The Effect of Combined Oral Contraceptive Pills on Factor VII Activity and D-dimer Level in Healthy and Obese Women - Abbas, Israa S.; Al-Rubaie, Haithem A.; Jaffar Alsaidissa, Jaffar N. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: The combined pill includes a combination of an estrogen and a progestin. Users of these pills have an increased risk of developing thrombotic disorders compared to the non-users. Obesity is an independent risk factor for venous thromboembolism. Obesity with oral contraceptive use increases the risk of thrombosis furthermore.Objectives: To assess the effects of these pills in obese and healthy non-obese women on factor VII activity and D-dimer level. Also to compare the thrombophilic effects of combined pills in women with control group of normal healthy non-users women.Patients and Methods: This study was started on November 2014 and completed on March 2015, and included 50 females attended at Baghdad Teaching Hospital. They were using contraceptive pills (Microgynon® ED Fe) for at least 3 months. Females were divided into 2 equal groups; the non-obese group and the obese group. As well 25 non-obese age-matched non-pregnant females not on contraception or taking any hormonal therapy were recruited as a control. The hemostatic parameters done for them included the prothrombin time, activated partial thromboplastin time, factor VII, D-dimer level, and platelet count.Results: There were significant reductions in prothrombin time in both the non-obese and obese groups compared to the control (P= 0.014 and 0.020, respectively). The correlations between the duration of pills use and clotting times both showed insignificant differences in the study groups. The factor VII activity in the non-obese and obese groups were significantly higher than that of the control (P= 0.041 and 0.001, respectively). There were also significant increase in D-dimer levels in the non-obese and obese groups compared to the control (P= 0.029 and 0.038, respectively). The platelet count was significantly increased only in the obese group compared to the control (P = 0.027).Conclusion: The use of the combined oral contraceptive pills (Microgynon® ED Fe) is associated with significant increase in factor VII activity and the level of D-dimer that may lead to enhanced procoagulant activity. Therefore, females should be properly assessed and monitored before starting using the pills and while on them.